The Acute Host-Response of Turkeys Colonized With Campylobacter coli - Sylte, Matthew J.; Sivasankaran, Sathesh K.; Trachsel, Julian; Sato, Yuko; Wu, Zuowei; Johnson, Timothy A.; Chandra, Lawrance C.; Zhang, Qijing; Looft, Torey (Frontiers in Veterinary Science, 2021)
Consumption of contaminated poultry products is one of the main sources of human campylobacteriosis, of which Campylobacter jejuni subsp. jejuni (C. jejuni) and C. coli are responsible for approximately 98% of the cases. In turkeys, the ceca are an important anatomical site where Campylobacter asymptomatically colonizes. We previously demonstrated that commercial turkey poults colonized by C. jejuni showed acute changes in cytokine gene expression profiles, and histological intestinal lesions at 2 days post-inoculation (dpi). Cecal tonsils (CT) are an important part of the gastrointestinal-associated lymphoid tissue that surveil material passing in and out of the ceca, and generate immune responses against intestinal pathogens. The CT immune response towards Campylobacter remains unknown. In this study, we generated a kanamycin-resistant C. coli construct (CcK) to facilitate its enumeration from cecal contents after experimental challenge. In vitro analysis of CcK demonstrated no changes in motility when compared to the parent isolate. Poults were inoculated by oral gavage with CcK (5x107 colony forming units) or sterile-media (mock-colonized), and euthanized at 1 and 3 dpi. At both time points, CcK was recovered from cecal contents, but not from the mock-colonized group. As a marker of acute inflammation, serum alpha-1 acid glycoprotein was significantly elevated at 3 dpi in CcK inoculated poults compared to mock-infected samples. Significant histological lesions were detected in cecal and CT tissues of CcK colonized poults at 1 and 3 dpi, respectively. RNAseq analysis identified 250 differentially expressed genes (DEG) in CT from CcK colonized poults at 3 dpi, of which 194 were upregulated and 56 were downregulated. From the DEG, 9 significantly enriched biological pathways were identified, including platelet aggregation, response to oxidative stress and negative regulation of oxidative stress-induced intrinsic apoptotic signaling pathway. These data suggest that C. coli induced an acute inflammatory response in the intestinal tract of poults, and that platelet aggregation and oxidative stress in the CT may affect the turkey’s ability to resist Campylobacter colonization. These findings will help to develop and test Campylobacter mitigation strategies to promote food safety in commercial turkeys.